Mr. Granite is from another planet! - Gutman, Dan; Paillot, Jim (New York, NY Scholastic Inc., 2015)
New third-grade teacher Mr. Granite has so many strange ideas about how to make Ella Mentary School environmentally friendly that the students are sure he must be an alien.
Originally published in 2008 by HarperCollins Children's Books.
Accelerated Reader/Renaissance Learning
110801
Keywords: Schools -- Juvenile fiction; Teachers -- Juvenile fiction; Green movement; Environmental protection; Life on other planets; Extraterrestrial beings; Humorous fiction; Juvenile works